Uncovering students' misconceptions by assessment of their written questions. Issue 1 (December 2016) - Olde Bekkink, Marleen; Donders, A.; Kooloos, Jan; de Waal, Rob; Ruiter, Dirk
Abstract Background Misconceptions are ideas that are inconsistent with current scientific views. They are difficult to detect and refractory to change. Misconceptions can negatively influence how new concepts in science are learned, but are rarely measured in biomedical courses. Early identification of misconceptions is of critical relevance for effective teaching, but presents a difficult task for teachers as they tend to either over- or underestimate students' prior knowledge. A systematic appreciation of the existing misconceptions is desirable. This explorative study was performed to determine whether written questions generated by students can be used to uncover their misconceptions. Methods During a small-group work (SGW) session on Tumour Pathology in a (bio)medical bachelor course on General Pathology, students were asked to write down a question about the topic. This concerned a deepening question on disease mechanisms and not mere factual knowledge. Three independent expert pathologists determined whether the content of the questions was compatible with a misconception. Consensus was reached in all cases. Study outcomes were to determine whether misconceptions can be identified in students' written questions, and if so, to measure the frequency of misconceptions that can be encountered, and finally, to determine if the presence of such misconceptions is negatively associated with the students' course formal examination score. A subgroup analysis was performed according to gender and discipline. Results A total of 242 students participated in the SGW sessions, of whom 221 (91 %) formulated a question. Thirty-six questions did not meet the inclusion criteria. Of the 185 questions rated, 11 % (n  = 20) was compatible with a misconception. Misconceptions were only found in medical students' questions, not in biomedical science students' questions. Formal examination score on Tumour Pathology was 5.0 (SD 2.0) in the group with misconceptions and 6.7 (SD 2.4) in the group without misconceptions (p  = 0.003). Conclusions This study demonstrates that misconceptions can be uncovered in students' written questions. The occurrence of these misconceptions was negatively associated with the formal examination score. Identification of misconceptions creates an opportunity to repair them during the remaining course sessions, in advance of the formal examination.